Analysis of land use changes of urban ventilation corridors in Warsaw in 1992-2015 - Osińska-Skotak, Katarzyna; Zawalich, Joanna (IGiPZ PAN, 2016)
One of the most important factors influencing a city’s climate is the ventilation of a given urban unit. The most effective avenue of wind penetration into a built-up area is provided by uninterrupted urban greenery, thoroughfares and railway land radiating from the city centre as well as river valleys cutting through the entire city creating a unified system. These areas are called urban ventilation corridors or urban ventilation wedges. In Warsaw such an air exchange and regeneration system has been under development since the XIX century. The aim of this paper is to illustrate the rate and direction of land use changes in 1992-2015 and indicate the cause of current changes in the development of ventilation corridors in Warsaw. Visual interpretation of SPOT and LANDSAT satellite images and aerial orthophotomaps provided the data source for a database on the state of development of the ventilation corridors in time series. The analysis carried out established that the built-up area mostly spreads at the expense of agricultural land, which can negatively influence the way the parts of ventilation system operate. Moreover, different analyses were conducted in order to discover the cause of the changes, including analysis of the local zoning plans which were in force at the time in question.
24 cm
Keywords: urban ventilation corridors; Warsaw; land use changes; LANDSAT; SPOT